Taxonomic revision of the Neotropical genus Caenopangonia Kröber, 1930 (Diptera: Tabanidae) - Krolow, Tiago Kütter; Henriques, Augusto Loureiro; González, Christian R. (Zootaxa, 2016)
The Neotropical species of Caenopangonia Kröber are revised herein based on examination of external and internal morphology of type material and specimens from Argentina and Chile. Three currently valid species are recognized: Caenopangonia aspera (Philip, 1958), Caenopangonia brevirostris (Philippi, 1865), and Caenopangonia hirtipalpis (Bigot, 1892). Two new species are described, Caenopangonia cerdai n. sp. Krolow, Henriques & González (Chile, Chacabuco) and Caenopangonia coscaroni n. sp. Krolow, Henriques & González (Chile, Malleco). We provide diagnosis and/or descriptions, distribution records, illustrations and discussion for all species, as well a key for identification.